UDС: 004.4; 621.315.1 Microcontroller-based remote monitoring of overhead power lines - Khayrullaev, Alisher (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. Due to the technical failure of the line, illegal connections, temperature rise in the cable occurring in the section between the electricity distribution point and the consumer meter of the overhead power lines, a number of difficulties arise in monitoring the energy consumption in the line. There are a number of ways to solve these problems, among which remote monitoring using modern IoT wireless sensors and microcontroller control devices gives effective results. Because this method is the basis of the SG (smart grid), which is widely used in the future. The main goal of this article is to design a monitoring device used in remote monitoring of the condition of low-voltage overhead power lines, classify the structure and characteristics of the sensors used in it, and do a comparative analysis of the modules used in the construction of the data transmission network. Methods. It is not possible to adequately monitor the condition of 0.4-6 kV transmission lines using ASCAE (automated system for control and accounting electricity). These methods can calculate the amount of energy coming out of the distribution transformer and the amount of power passed through the consumer meter. Therefore, this paper proposed a remote monitoring method based on microcontroller control for real-time monitoring of the status of low-voltage overhead power lines. Results. As a result of the research, a remote monitoring device was designed, capable of transmitting the results obtained from voltage, current and temperature sensors in real time from two wireless transmission modules. This device transmits data to the concentrator using ZigBee, and it transmits data to the monitoring center through the GSM module. In addition, the microcontroller control unit in the device takes into account the geographic location of the object and the synchronized time. Conclusion. The system, which is organized using a remote monitoring device, prevents technical failures that may occur in low-voltage overhead power transmission lines, the current parameters of the line (voltage, current, cable temperature, wind speed, phase) and unexpected to the line (the unregistered-illegal connection) provides opportunities to send real-time information about downloads.